2017
DOI: 10.1371/journal.pone.0179633
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyopathy development protection after myocardial infarction in rats: Successful competition for major dihydropyridines’ common metabolite against captopril

Abstract: During the last 25 years angiotensin-converting enzyme inhibitors spectacularly conquered the field of cardiovascular diseases therapy. Nevertheless, lack of new studies concerning side effects associated with their chronic administration seems to be rather confusing. In our previous research, we proved that the main furnidipines’ metabolite (M-2) possess multiple cardioprotective actions. Currently, we compared effects of post-infarction long-term oral treatment with M-2 and captopril on hemodynamic parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 55 publications
(73 reference statements)
1
1
0
Order By: Relevance
“…CAP was implied to attenuate cardiac apoptosis and hypertrophy induced by TAC, which could be attributed to the inhibition of the Wnt3a/β‐catenin and the JAK2/STAT3 signalling pathway, respectively 7 . The anti‐hypertrophy role of CAP was validated in our study, however, side effects like coughing, nephrotoxicity and marked hemodynamic impact were inevitable when applying CAP to treating hypertension 27–29 . The present study showed the anti‐fibrotic effect of PFD was not inferior to CAP, which implied great potential in preventing cardiac remodelling and heart failure induced by hypertension without modulating blood pressure.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…CAP was implied to attenuate cardiac apoptosis and hypertrophy induced by TAC, which could be attributed to the inhibition of the Wnt3a/β‐catenin and the JAK2/STAT3 signalling pathway, respectively 7 . The anti‐hypertrophy role of CAP was validated in our study, however, side effects like coughing, nephrotoxicity and marked hemodynamic impact were inevitable when applying CAP to treating hypertension 27–29 . The present study showed the anti‐fibrotic effect of PFD was not inferior to CAP, which implied great potential in preventing cardiac remodelling and heart failure induced by hypertension without modulating blood pressure.…”
Section: Discussionsupporting
confidence: 51%
“…7 The anti-hypertrophy role of CAP was validated in our study, however, side effects like coughing, nephrotoxicity and marked hemodynamic impact were inevitable when applying CAP to treating hypertension. [27][28][29] The present study showed the anti-fibrotic effect of PFD was not inferior to CAP, which implied great potential in preventing cardiac remodelling and heart failure induced by hypertension without modulating blood pressure. In addition, our study provided a solid foundation for future clinical studies developing novel anti-fibrotic agents in hypertension.…”
Section: Wang Et Al Found Pfd Inhibited Cardiac Fibrosis By Suppressingmentioning
confidence: 87%